Atractivos y desarrollo turístico de la parroquia San Juan, cantón Riobamba, provincia de Chimborazo. - Guaman Paca, Cristhian Dario (2023)
“San Juan”, a place of unparalleled natural and cultural beauty, this parish captivates locals and strangers to know the wealth it has in its corners, known as the guardian of Chimborazo and the closest point to the sun in its vicinity protects the majestic Chimborazo Volcano. In this parish you can distinguish different tourist attractions of great relevance as well as its exquisite cuisine, this research work aims to analyze the relationship between the attractions and tourism development of the “San Juan” parish, Riobamba canton, Chimborazo Province. It is worth mentioning that the “Gobierno Autónomo Descentralizado Parroquial Rural de San Juan” does not have an adequate planning that allows the use of these tourist resources. With the information obtained, it was possible to apply the research instruments, which were validated by the group of experts from the “Universidad Nacional de Chimborazo”, whose results allowed to know the perception of the tourist attractions offered by the parish of San Juan. Finally, with the data obtained, a proposal was made for a digital tourist guide, focusing on local and national tourists. This guide will serve as a support tool for the “Gobierno Autónomo Descentralizado Parroquial Rural de San Juan”, which will promote and disseminate the tourist attractions of the parish in an efficient manner.